Impact assessment of waterway development on the socioeconomic conditions and ecosystem in the upper Yangtze River. (23rd February 2022) - Li, Wenjie; Wu, Jianping; Du, Hongbo; Wan, Yu; Yang, Shengfa; Xiao, Yi; Wang, Li
Abstract: The waterway from Chongqing to Yibin in the upper Yangtze River provides strong support for the socioeconomic development in Western China, while it also has a negative influence on the river ecosystem, such as river fragmentation, wetland disconnectivity, fish habitat, and biodiversity. Accurately characterizing the exploitation, economic efficiency, and ecological pressure of the waterway from Chongqing to Yibin is of great significance for the further development of the upper Yangtze River. In this study, based on statistical data from the National Bureau of Statistics of China, the waterway development, economic benefits, and ecological pressure of the waterway from Chongqing to Yibin were evaluated. The sustainability index (SI) was introduced to comprehensively assess the sustainability of waterways using the hierarchical model, which integrates the exploitation ratio (ER), economic efficiency index (EEI), and ecological pressure index (EPI). A relatively low ER (41.04%), a low consistency index (CI, 0.31), a high EEI (9037.18 USA/gha), and a low EPI (0.33) yielded an SI of 0.70, indicating that the waterway from Chongqing to Yibin in the upper Yangtze River is in a sustainable development stage. Compared with the typical global Golden Inland Waterways, the waterway from Chongqing to Yibin still has great development potential under the prioritizing ecological protection.